From rights to duties: The ethical imprint of human rights based on the responsibility to protect - Bonet de Viola, Ana María (2020)
The objective of this work is to propose, from an ethical perspective, a rethinking of the principle of “responsibility to protect”.  It starts from the premise that the violence generated by the intervention on any alterity is a reflection of the modern roots of contemporary rights and its individualistic postulates, based on the extreme defense of identity.  It is proposed to review these postulates through a reformulation of the legal concept of responsibility to protect, in order to propose an ethical approach to human rights, as rights of alterity. This means, in definitive, a rethinking of the terms of global coexistence: sociality is not constituted by addition of identities, but as an excess of responsibilities.